A comprehensive review on intelligent torque vectoring control for electric vehicle - F Vanlalhriatpuia; Ksh Robert Singh; Amarendra Matsa; Subir Datta; Md. Minarul Islam; Taha Selim Ustun (Energy Exploration & Exploitation)
Vehicle dynamic control (VDC) is an important study where the vehicle performance, handling, stability, and statistics of the vehicle can be recorded to improve performance. Torque vectoring controller (TVC) a form of VDC is used to improve vehicle handling and driving in extreme situations by correcting oversteer and understeer conditions, this TVC is used in EV to reduce the consumption of the battery by reducing the general energy use. In TVC, it is broadly classified to classical and intelligent methods where classical methods used a two-stage optimization method via a high and low level controller while intelligent torque vectoring controller (ITVC) methods uses artificial intelligence (AI) based methods like soft computing, machine learning and other AI methods to enhance vehicle performance and efficiency. Each ITVC is reviewed where the advantages, disadvantages and applications of each controller is compared. The study also shows the timeline of ITVC development showing every existing ITVC method being conducted, it also shows the complexity, vehicle stability, braking performance, lateral stability, mechanical energy consumption and energy conversation between the different ITVC methods.